If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 = y + -22 Reorder the terms: -18 = -22 + y Solving -18 = -22 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. -18 + -1y = -22 + y + -1y Combine like terms: y + -1y = 0 -18 + -1y = -22 + 0 -18 + -1y = -22 Add '18' to each side of the equation. -18 + 18 + -1y = -22 + 18 Combine like terms: -18 + 18 = 0 0 + -1y = -22 + 18 -1y = -22 + 18 Combine like terms: -22 + 18 = -4 -1y = -4 Divide each side by '-1'. y = 4 Simplifying y = 4
| -x^2+29x-54=0 | | x+.15x+2.4=2(x-1.3) | | 1+5y=4 | | 25a+125=28a | | T-17.9=-31.05 | | 3(x-5)-(2x+4)=-x+7 | | 2y-12=-33+3 | | 2x+4=2/3x | | 2x+2=40.3 | | 6+5c=-28 | | ln^2(x)+(5)ln(x)=14 | | 3x^2-90=1362 | | 4.8f+6.4=(-8.48) | | T+106.7=62.3 | | ax-ay=b | | 20-2w=4(15-w) | | 7f+2f=18 | | T+20.4=-15.7 | | -x^2+19x-48=0 | | 0=12x-15 | | v-2v+8=8+2v+v | | -2+5x+7x=-14 | | -x^2+19-48=0 | | -8+88g=56 | | -2=11+3(3(1)-5)-7(1) | | 8=6x+2 | | -6x+13=2f+13 | | 26=14-4x | | 6x+2+x=65 | | 15.75n=378 | | d+2d+3d=12 | | 15w+10=70 |